Gender by Judith Butler (A Comparative Analytical Content Study to Understand the Concept of Gender between the West and Kurdistan) - حسێن, م. د. هەتاو حمەساڵح; Hussein, L.Dr.Bekhal Abubakr (Sulaimani Journal for Humanities, 2026)
In recent years, the concept of gender has intensively entered Kurdistan and has caused a lot of debate among academics and intellectuals. Some see her as the savior and solution to all women's complex problems, while others see her as a destroyer of culture, religion and values of societies. In this analytical study, our aim is to read Judith Butler's gender thought as one of the gender theorists. In this regard, Butler's areas of gender thought are highlighted: Sex Stability, Sex Performance, Non-binary system, Gender Spectrum, Queers. Each of these concepts is currently being worked on in the West and is expected to develop in Kurdistan in the next few years, especially in the current era of new media and technology that there are no limits or obstacles to the spread and communication of ideas. The method used in this study is a content analysis of Butler's writings, and the analysis materials include most of Butler's own published papers in the West. In the next step, a comparison between Butler's and Kurdish writers' views on the concept of gender was conducted through group discussions with five university professors, in order to obtain the views of academics and feminist activists to understand the differences in understanding and working for gender ideology in West and Kurdistan.
Keywords: Butler; Gender; Sex; Feminism